Optimization of Dialogical Patrol by the Sukoharjo Samapta Patrol Unit in Preventing the Crime of Motor Vehicle Theft - Fadiral, Yoki Abhiesta (Advances in Police Science Research Journal, 2024)
Motor Vehicle Theft (PENCURIAN KENDARAAN BERMOTOR) often dominates in the records of social security disturbances cases in the territory of Polres Sukoharjo jurisdiction. Thus, the Polres Sukoharjo, through the Samapta Units, has a role in controlling and crime preventing by taking preventive measures in the form of the dialogical patrol. The implementation of dialogical patrol is quite efficient but not yet fully optimal. This can be seen from the thief index in this territory still fluctuating in its monthly period. This situation encourages researcher to deepen research with the topic of optimizing the Dialogical Patrol to prevent Motor Vehicle Theft in the teritory of Polres Sukoharjo jurisdiction. The final results of this study found a series of symptoms in the form of achieving consistency of dialogical patrol, marked by the fulfillment of the standardization of patrol. This patrol is good enough effective if looked by the process, but have not shown optimal results on a larger scale. This is influenced by internal factors which is strengths and opportunities and external factors which is weaknesses and threats, so that several efforts are needed to optimize the dialogical patrol to achieve the planned results.